PENGARUH MOTIVASI KERJA DAN PARTISIPASI GURU DALAM MGMP SERTA KEMAMPUAN KOMPETENSI PEDAGOGIK GURU TERHADAP KINERJA GURU PENJASORKES DI SMA SE-KABUPATEN SUMEDANG - Asep Suhayat (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2022)
This research aims to find out the influence of work motivation and teacher participation in MGMP as well as the ability of teacher pedagogical competence on the performance of teachers in high school in Sumedang Regency. This research is an ex-post facto study with a quantitative approach. Data is analyzed with qualitative descriptive techniques. The results showed that there was a positive and significant influence: (1) mgmp partition on the performance of high school teachers in Sumedang Regency which was indicated by a value of rx1y of 0.272, r??x1y of 0.074, thitung value greater than ttabel of 2,400 > 1.71714, and MGMP participation was in the low category of 7.4%; (2) the teacher's work motivation towards the performance of high school teachers in Sumedang Regency indicated by a value of rx1y of 0.322, r??x1y of 0.103, a thitung value greater than a level of 2.882 > 1.71714, and teacher work motivation is in the low category of 10.3%;(3) pedagogical competence to the performance of high school teachers in Sumedang Regency indicated by a value of rx2y of 0.426, r??x2y of 0.151, thitung greater than ttabel of 4.970 > 1.71714, and pedagogical competence is in the less than optimal category of 15.1%;(4) MGMP participation, teacher work motivation and pedagogical competence together to the performance of high school teachers in Sumedang Regency indicated by R of 0.377, R2 of 0.142, Fhitung value greater than Ftabel of 3,868 > 2.73,and teacher performance is in the less than optimal category of 14.2%. Mgmp participation variables had a contribution relative to teacher performance of 7.4%, teacher work motivation had a contribution relative to teacher performance of 10.3% and pedagogical competency variables had a contribution relative to teacher performance of 15.1%.